Unplanned readmissions in younger and older adult patients: the role of healthcare-related adverse events - Magdelijns, Fabienne J. H. (Eur J Med Res, 2016)
BACKGROUND: Readmissions are a burden for patients and increase healthcare costs. In Europe, factors associated with readmissions have not yet been extensively investigated. This study aimed to discover factors associated with readmissions in both young and older adult internal medicine patients. Furthermore, we explored the role of healthcare-related adverse events (AEs) in readmissions. METHODS: All patients admitted through the emergency department to the internal medicine department in the last 2 weeks of each month (2011) were included. Information on index admissions and readmissions, defined as an unplanned admission within 30 days after discharge, was obtained from the electronic patient record system. Demographic, clinical, and organizational factors were evaluated for their association with readmissions. RESULTS: Of all patients (n = 940), 17.3 % were readmitted; 16.9 % of the younger (<65 years, n = 485), and 17.8 % of the older patients (≥65 years, n = 455). Dependency in activities of daily living (ADL) was the only factor associated with readmissions in both all ages (OR 2.43) and in older patients (OR 3.19), while age was associated with readmissions in younger patients (OR 1.03 per year). AEs leading to 35.4 % of all index admissions were not associated with readmissions. CONCLUSIONS: Readmissions are common in medical patients, and, thus, remain a reason for concern in terms of patient safety and quality of care. AEs, responsible for to the index admission, were not associated with readmissions. ADL dependency was the only factor associated with readmission in patients of all ages and older patients, indicating that determining which patients are at risk for readmissions is not easy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40001-016-0230-0) contains supplementary material, which is available to authorized users.